2021
DOI: 10.1016/j.esxm.2021.100399
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Patient Satisfaction With the Low-Cost, Semi-Rigid Shah Penile Prosthesis: A boon to the Developing Countries

Abstract: Introduction In developing countries most patients with refractory erectile dysfunction cannot afford a penile prosthesis (PP) due to its cost and non-coverage by insurance companies. Aim To assess the patient satisfaction outcomes with a novel, low-cost, semi-rigid PP. Methods 52 patients who had received the Shah semi-rigid PP between January 2013 and December 2018 were included in this bidirectional study. Patient demographics including ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…First, although our institution has a high-volume of patients undergoing PPS, all patients did not complete an EDITS questionnaire. Like as mentioned above, utilizing a validated survey in assessing sexual and device satisfaction is important when evaluating PPS patients (9,36,37). Many PPS satisfaction studies are limited by using non-validated assessments in capturing data.…”
Section: Discussionmentioning
confidence: 99%
“…First, although our institution has a high-volume of patients undergoing PPS, all patients did not complete an EDITS questionnaire. Like as mentioned above, utilizing a validated survey in assessing sexual and device satisfaction is important when evaluating PPS patients (9,36,37). Many PPS satisfaction studies are limited by using non-validated assessments in capturing data.…”
Section: Discussionmentioning
confidence: 99%
“… 23 To date, three reports have been published with the Shah penile prosthesis; a single case report in a neophallus 24 while the other study showed good residual penile tumescence in 50% of cases and more than 90% of patients reported no problem with device concealment. 25 In another paper comparing Shah’s device and AMS 650 prostheses, there were no significant differences reported in the ED Inventory of Treatment Satisfaction (EDITS) questionnaire and EDITS partner survey at 80.66 ± 4.49 and 75.66 ± 6.57, respectively, at 12 months after surgery and 71.73 ± 8.10 and 65.6 ± 6.49, respectively, at 24 months after surgery. 26 Major and minor postoperative complications were seen in 10.7% (one infection, one urethral injury and one impending erosion) and 21.4% (6/28) of patients, respectively.…”
Section: Malleable Prosthesis Implants: Clinical Datamentioning
confidence: 97%
“…23 To date, three reports have been published with the Shah penile prosthesis; a single case report in a neophallus 24 while the other study showed good residual penile tumescence in 50% of cases and more than 90% of patients reported no problem with device concealment. 25…”
Section: Shah Malleable Prosthesis (Surgiwear)mentioning
confidence: 99%